Prevention and improved management of serious neurological adverse events during praziquantel-based mass drug administration in a Taenia solium endemic area: Experiences from Madagascar. - José Alphonse Nely; Noromanana Sylvia Ramiandrasoa; Diana Edithe Andria-Mananjara; Glenn Edosoa; Patricia Rasoamihanta Martin; Bernadette Abela; Meritxell Donadeu; Agnès Fleury (PLoS Neglected Tropical Diseases)
Mass drug administration (MDA) programs involving praziquantel are used in public health programs to control diseases such as schistosomiasis, taeniasis caused by Taenia solium, opisthorchiasis and clonorchiasis. Praziquantel is a systemically distributed anthelmintic drug also used to treat neurocysticercosis (NCC) caused by the larval stages of T. solium in the central nervous system. The doses of praziquantel used in MDA are low compared to those used for the treatment of NCC, but in people with latent NCC (without symptoms or signs), there is a potential risk of neurological adverse events (AE) due to the development of inflammation around the cysts following administration. In Madagascar two large MDA campaigns aimed at T. solium were conducted using praziquantel in the Vakinankaratra region. Prior to the first MDA campaign, we implemented a program designed to minimize the occurrence of neurological AE and improve their management, which included training of health agents and community workers as well as health centres staff, population awareness, post-MDA active and passive surveillance and the supply of basic medicines to health centres. This program was repeated for the second MDA campaign. A total of 117,216 and 163,089 people were treated during the first and second MDA campaign respectively, with 10 participants experiencing serious AE, which were successfully managed. The beneficial results from our program in Madagascar can help other programs and countries using MDA with praziquantel in T. solium endemic areas to improve the safety of these campaigns.